2016
DOI: 10.1128/genomea.00651-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Causative Antigen of Summer-Type Hypersensitivity Pneumonitis, Trichosporon domesticum JCM 9580

Abstract: Here, we report the draft genome sequence of Trichosporon domesticum JCM 9580, isolated from the house of a patient with summer-type hypersensitivity pneumonitis (SHP) in Japan. This genomic information will help elucidate the mechanisms of the development of SHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Recently, several Trichosporonales were studied with respect to their biotechnological properties, including the oil-accumulating C. oleaginosum, which was first isolated from a dairy plant, and has the ability to metabolize chitin-rich and other non-conventional substrates [44][45][46][47]. The sequenced C. oleaginosum strain is haploid and similar in genome size and gene content to strains from the sister order Tremellales; this is also the case for several other Trichosporonales genomes that have since been sequenced [28,46,[48][49][50][51][52]. Interestingly, C. oleaginosum showed some similarities to C. neoformans in the organization of MAT loci.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, several Trichosporonales were studied with respect to their biotechnological properties, including the oil-accumulating C. oleaginosum, which was first isolated from a dairy plant, and has the ability to metabolize chitin-rich and other non-conventional substrates [44][45][46][47]. The sequenced C. oleaginosum strain is haploid and similar in genome size and gene content to strains from the sister order Tremellales; this is also the case for several other Trichosporonales genomes that have since been sequenced [28,46,[48][49][50][51][52]. Interestingly, C. oleaginosum showed some similarities to C. neoformans in the organization of MAT loci.…”
Section: Introductionmentioning
confidence: 93%
“…Since the analysis of the first C. oleaginosum genome, several more Trichosporonales genomes have been sequenced, although none were analyzed with respect to their MAT loci [28,[48][49][50][51][52][53]. Here, we describe the sequencing of two additional Trichosporonales genomes for C. oleaginosum ATCC20508 and Vanrija humicola CBS4282, and the analysis of MAT loci organization in Trichosporonales genomes from 24 different species.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, genome sequences have been published for Trichosporonales species from the genera Apiotrichum, Cutaneotrichosporon, Takashimella, Trichosporon, and Vanrija [45][46][47][48][49][50][51][52] ( Table 1). We analyzed the genomes of 29 isolates that belong to 24 Trichosporonales species for the organization of the MAT loci, and found that all of them contain fused MAT loci, with both mating-type determining genes (STE3 and SXI) located ~55 kb apart from each other.…”
Section: Trichosporonales Species Have Fused Hd and P/r Mating Type Locimentioning
confidence: 99%
“…Recently, several Trichosporonales were studied with respect to their biotechnological properties, including the oil-accumulating C. oleaginosum, which was first isolated from a dairy plant, and has the ability to metabolize chitin-rich and other nonconventional substrates [41][42][43][44]. The sequenced C. oleaginosum strain is haploid, and similar in genome size and gene content to genomes from the sister order Tremellales, and this was also the case for several other Trichosporonales genomes that have since been sequenced [43,[45][46][47][48][49][50]. Interestingly, C. oleaginosum showed some similarities to C. neoformans in the organization of MAT loci.…”
mentioning
confidence: 92%
See 1 more Smart Citation